Binaural Audio and 360 Video: Immersive Method of Preserving Banten's Culture and History - Jason Obadiah (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
Visual media is an easy-to-use medium for documenting events, discoveries, and even the culture of a particular country. It's different with audio media, where audio media is very difficult to describe something like a culture without someone having had experiences related to that culture. Binaural audio is an audio system where the system allows a person to record audio that can represent the auditory results of the ear organs. If a person is presented with a binaural audio of a cultural performance, then the audio can simulate a person's perception as if he is at that cultural performance. Over time, the preservation of culture and history is needed so that Indonesian culture and history remain known in this increasingly modern era. The combination of visual media such as 360 Video with binaural audio media is expected to attract people to be more curious about Indonesian culture and history and appreciate it more as well as open the possibility for people with disability to experience the historical location through 360 video or Virtual Reality. This research is a means to documenting and preserve the Chinese Indonesian shrine across Indonesia’s island starting from Banten province.Binaural Audio dan Video 360: Metode Imersif Melestarikan Budaya dan Sejarah Banten Abstrak Media visual adalah media yang mudah digunakan untuk mendokumentasikan peristiwa, penemuan, dan bahkan budaya suatu negara tertentu. Berbeda dengan media audio, di mana media audio sangat sulit untuk menggambarkan sesuatu seperti budaya tanpa seseorang memiliki pengalaman yang berkaitan dengan budaya tersebut. Audio binaural adalah sistem audio di mana sistem tersebut memungkinkan seseorang untuk merekam audio yang dapat mewakili hasil pendengaran organ telinga. Jika seseorang disajikan dengan audio binaural dari pertunjukan budaya, maka audio tersebut dapat mensimulasikan persepsi seseorang seolah-olah dia berada di pertunjukan budaya itu. Seiring berjalannya waktu, pelestarian budaya dan sejarah sangat dibutuhkan agar budaya dan sejarah Indonesia tetap dikenal di era yang semakin modern ini. Kombinasi media visual seperti 360 Video dengan media audio binaural diharapkan dapat menarik minat masyarakat untuk lebih penasaran dengan budaya dan sejarah Indonesia dan lebih mengapresiasinya serta membuka kemungkinan bagi penyandang disabilitas untuk merasakan lokasi bersejarah tersebut melalui video 360 atau Virtual Reality. Penelitian ini adalah sarana untuk mendokumentasikan dan melestarikan kuil Cina Indonesia di seluruh pulau Indonesia mulai dari provinsi Banten.